(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The research aims to identify small and medium enterprises in accounting thought in terms of definition and concept, and this international financial reporting standard for small and medium-sized enterprises (SMEs) in the theoretical aspect. As for the practical aspect, the small and medium-sized enterprises standard has been applied to the financial statements of the company in question, the preparation of the opening entry on the date of the transition, the requirements of measurement and the accounting disclosure on the date following the application of the standard, and the preparation of the company’s financial statements and the accompanying explanations according to the standard of small and medium-sized enterprises. The research reached a set of conclusions, the most prominent of which is. The emergence of fundamental differences between the applications of the small and medium-sized enterprises standard on the one hand and the applications of the unified accounting system on the other hand, and this is what appears in the table of the impact of adopting the International Financial Reporting Standard for Small and Medium Enterprises before and after implementation. Simplifying the accounting measurement and disclosure requirements within the SMEs standard enables Iraqi companies to apply it and thus prepare globally comparable financial statements, which increases the chances of foreign companies entering to invest in Iraq. The research recommended the necessity of developing an effective system for the transition to the international financial reporting standard for small and medium-sized enterprises and removing the obstacles that face small and medium enterprises when implementing it.